Penjadwalan Tenaga Kerja pada Unit Ambulans Di Industri Pengolahan Migas (Aplikasi Metode Alghorytma Monroe) - Cece Hadian; Dudang Aliansyah; Tri Sukmono; Kohar Sulistyadi; Vitri Dyah Herawati (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2019)
Quality improvement in ambulance services to deliver optimal health care to client is very important. In order to provide optimal service XYZ Company strives to make integrated planning including of scheduling preparedness. The aim is to provide ambulance personel comfort that it will improve the work ethic and effort. In this research, the author tries to apply the Alghorytme Monroe method to get fair scheduling with 5 working days and 2 consecutive holidays (Regullar Days Off) to replace the previous scheduling of 6 working days and 2 days off. The result is not suitable, there is a minimum increase in the number of workers required as many as 8 people from the actual number of existing workforce, so that this model cannot be applied to XYZ companies because it will increase costs.